Ber Grafting in Banaskantha Division - Joshi, N. J. (Indian Forester, 1960)
During 1958-59 ber grafting was done in Banaskantha division in an area of 5 acres as an experiment. The results were very good. The article gives the details of the procedure adopted for ber grafting as also its financial implications.